EDUKASI GIZI SEIMBANG PADA ANAK SEKOLAH DASARDI KECAMATAN CILINCING JAKARTA UTARA - Palupi, Khairizka Citra; Sa’pang, Mertien; Swasmilaksmita, Prita Dhyani (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractNutrition transition contribute to doubke burden of nutrition problems in Indonesia. The Nutrition screening in several primary schools in the District of Cilincing, North Jakarta showed that the prevalence of malnutrition was 28%, in which the prevalence of obesity was 3 times higher than the prevalence of wasting.Malnutrition may disrupt the process of growth and development of children, increase the risk of disease and hospital costs. Based on the discussion with stake holder of elementary school, students need to be given nutrition education because there has never been any nutrition education before. The purpose of this study is to educate balanced nutrition among school-age children and their teacher. Methods: Preparation of activities was carried out in March 2018. The implementation of nutrition education was conducted in April 2018 at SD Rorotan 03 and SD Rorotan 07, Cilincing District, North Jakarta. The material consisted of Ã¢â‚¬Å“Tumpeng Gizi SeimbangÃ¢â‚¬Â (TGS), Ã¢â‚¬Å“10 Pesan Gizi SeimbangÃ¢â‚¬Â and TGS Puzzles. Results: Balanced nutrition education increased knowledge, attitudes and behavior among elementary school students. Nutrition education through TGS puzzle games also increased their knowledge and attitude towards balanced nutrition. Participants know what foods are included in the staple food, protein sources, vegetables and fruit. Conclusion: Nutrition education is quite effective program to improve knowledge, attitude and behavior towards balanced nutrition among elementary school children.Ã‚Â Keywords : nutrition education, elementary school, balanced nutritionÃ‚Â AbstrakTransisi gizi memicu Indonesia mengalami beban ganda masalah gizi. Hasil skrining gizi pada beberapa sekolah dasar di Kecamatan Cilincing, Jakarta Utara menunjukkan prevalensi malnutrisi 28% dimana prevalensi kegemukan 3x lebih tinggi dibandingkan dengan prevalensi kurus. Malnutrisi mampu menganggu proses pertumbuhan dan perkembangan anak, meningkatkan risiko penyakit serta meningkatkan pengeluaran untuk biaya rumah sakit. Berdasarkan pertemuan bersama pihak sekolah, siswa Ã¢â‚¬â€œ siswi di sekolah dasar tersebut perlu diberikan edukasi gizi karena belum pernah ada edukasi gizi sebelumnya. Tujuan penelitian ini adalah memberikan pemahaman kepada anak usia sekolah dan pihak sekolah mengenai gizi seimbang. Metode:Persiapan kegiatan dilakukan pada bulan Maret 2018. Pelaksanaan edukasi gizi dilakukan pada bulan April 2018 di SD Rorotan 03 dan SD Rorotan 07. Materi terdiri dari Tumpeng Gizi Seimbang (TGS), 10 Pesan Gizi Seimbang dan Puzzle TGS. Hasil Penelitian: Pemberian edukasi gizi metode ceramah terbukti efektif meningkatkan tingkat pengetahuan, sikap dan perilaku siswa sekolah dasar. Edukasi gizi melalui permainan puzzle TGS menunjukkan menunjukkan bahwa peserta mengalami peningkatan pengetahuan akan gizi seimbang. Peserta mengetahui apa saja makanan yang masuk dalam kelompok makanan pokok, lauk, sayur dan buah. Kesimpulan: edukasi gizi seimbang cukup efektif dalam meningkatkan pemahaman tentang gizi seimbang pada anak Sekolah Dasar.Ã‚Â Kata kunci : edukasi gizi, sekolah dasar, gizi seimbang